Predicting illness anxiety symptoms based on worry, alexithymia, intolerance of uncertainty and cognitive emotion regulation strategies - Vida Oshrieh; Mohammad Ali Besharat; Masoud Gholamali Lavasani (مجله علوم روانشناختی)
Background: Illness Anxiety Disorder (IAD), is a type of worry about the existence or occurrence of serious medical diseases. worry, alexithymia, intolerance of uncertainty and cognitive emotion regulation strategies can be effective factors in the development and persistence of mental disorders such as illness anxiety. Since individuals with IAD suffer from many problems, identifying the influencing and predicting factors of IAD simultaneously in research are considered important. Aims: The purpose of the present study was to predict illness anxiety symptoms based on worry, alexithymia, intolerance of uncertainty and cognitive emotion regulation strategies. Methods: The present study was descriptive correlation and the statistical population included all people living in Tehran between the ages of 20 and 60 in 2021. A total of 414 individuals (344 females, 70 males) participated in the study. Participants were asked to complete the Illness Anxiety Scale (Besharat, 2011), Penn State Worry Questionnaire (Meyer et al., 1990), Toronto Alexithymia Scale-20 (Bagby et al., 1994), Intolerance of Uncertainty Scale (Carleton et al., 2007) and Cognitive Emotion Regulation Questionnaire (Garnefski & Kraaij, 2007). The data were analyzed by Pearson correlation coefficient and stepwise regression methods by SPSS27. Results: worry, alexithymia, intolerance of uncertainty and maladaptive emotion regulation strategies had a significant positive association with illness anxiety symptoms (P< 0.05). This result was reversed for adaptive emotion regulation strategies; revealing that this type of strategies had a significant negative association with illness anxiety symptoms (P< 0.05). Furthermore, the cognitive emotion regulation strategies were removed from the model due to the lack of predictive power, but worry, alexithymia and intolerance of uncertainty have the ability to predict the illness anxiety symptoms. Conclusion: Based on the research findings, worry, alexithymia and intolerance of uncertainty can predict illness anxiety symptoms. These results can be useful in the prevention, diagnosis and treatment of IAD.